Margrethe Hald: the quest for the tubular loom - Mokdad, Ulrikka; Grymer-Hansen, Morten (Archaeological Textiles Review, 2021)
The aim of this paper is to shed light on the research and travels of the pioneering Danish textile researcher Margrethe Hald regarding the rare and ancient warping technique known as the tubular loom. It retraces Hald’s steps on her quest for the tubular loom from the study of Danish bog finds through Egyptian textile remains to surviving weaving traditions in Syria and South America. Hald’s method of combining archaeology, ethnology, textile craft, and art history in her research created new understandings of past and present textile traditions and paved the way for modern interdisciplinary research. By revisiting Hald’s published and unpublished work on the subject, as well as letters and notes, this paper demonstrates how archival studies can improve understanding of the work carried out by early textile researchers.